Distinguishing: Appointment, Recognition of Children and Ratification of Children Based on Law Number 23 of 2006 concerning Population Administration - Habib Adjie (GoAcademica Research & Publishing, 2021)
Article 4 7(1) of Law No 23 of 2006 on the Administration of the Population (Adminduk) provides that the adoption of children is a legal act to transfer the rights of the child from the families of parents, legal guardians and others responsible for the care, education and bringing of children into the families of their adoptive parents by decision of the Court Basing this child acceptance on the concept or limitation of child adoption is a legal act with certain law-controlled goals and aims and inevitable legal consequences, such as the bodily and psychological responsibility of the child he or she accepts. Kid Recognition is a father's recognition of his kid born from lawful marriage with the agreement of the biological mother of the child. Kid acknowledgment is meant to provide the child a biological father/father, as well as legal civil ties. The provisions mentioned in the Elucidation of Article 49(1) of the Adminduk Law are acknowledgments that can only be made by the father/father, in this case there is no mother's acknowledgement; in other words, it is not automatically necessary to prove that the child was not born by the mother concerned. Elucidating Article 50(1) of the Child Legalization Administration Law is the ratification of the status of a child born outside the legal marital bond while registering the marriage of the child's two parents. Article 50(1) of the Administrative Law requires parents to notify the child's ratification to the Implementing Agency no later than 30 (thirty) days after the child's father and mother marry and acquire a marriage certificate. Child Recognition or Child Ratification can be performed for children born outside formal marriage. If the child's acknowledgement is restricted to a disclosure from his biological father, accepted by his birth mother, without being followed by the parents' marriage, yet in the Child Legalization, the child's mother and father are married. When documenting the wedding, the youngster is recognized as their biological kid. And this kid's ratification is a legal endeavor (rechtsmiddel) to offer a position as a legitimate kid through marriage by his parents.